Regulation of expression of unintegrated and integrated HIV-1 DNA: keeping the wolves at bay - Goff, Stephen P. (Frontiers in Virology, 2024)
The unintegrated HIV-1 DNAs formed by reverse transcription in the early hours after infection are subject to profound transcriptional silencing. The repression of expression of foreign DNA, as an aspect of the innate immune system, serves to restrict the activity of many invading pathogens. Newly formed retroviral DNAs are rapidly loaded with histones upon entry into the nucleus, and the repression of their expression is mediated by an array of host proteins that introduce histone modifications characteristic of heterochromatin, including histone methylation and histone deacetylation. Knockout or knockdown of expression or inhibition of these host factors can relieve the silencing, allowing for viral gene expression even in settings where HIV-1 DNA integration is blocked. When viral DNA integration is allowed, forming the integrated provirus, the silencing in most cases is dramatically relieved, leading to high levels of expression and formation of progeny virus. In some settings and cell types, silencing of the integrated DNA is maintained, or re-established, such that the infected cells retain a silent copy of the viral DNA without production of progeny virus. The basis for the typical switch from silent DNA to actively expressed DNA upon integration is not yet fully clear. This review will summarize the current understanding of the regulation of expression of unintegrated HIV-1 DNAs and the nature of the chromatin that is formed on the viral DNA, and will especially focus on the host machinery that establishes repressive heterochromatin-like structures on the unintegrated DNA. The activation of expression that normally occurs upon integration, and the special circumstances when viral DNA expression is not activated, will also be discussed. These cases can result in the formation of populations of infected cells carrying silent proviruses, which persist for decades in infected individuals in spite of antiviral therapy. This pool of latently infected cells can be stochastically reactivated to give rise to spreading virus whenever antiviral drugs are withdrawn, and constitute the barrier to a true “cure” of AIDS. The hope is that a deeper understanding of the regulation of expression of viral DNAs will lead to new means to prevent or control viremia and disease.